ZapE is a novel cell division protein interacting with FtsZ and modulating the Z-ring dynamics. - Marteyn, B; Karimova, G; Fenton, A; Gazi, A; West, N; Touqui, L; Prevost, M; Betton, J; Poyraz, O; Ladant, D; Gerdes, K; Sansonetti, P; et al. (American Society for Microbiology, 2014)
Bacterial cell division requires the formation of a mature divisome complex positioned at the midcell. The localization of the divisome complex is determined by the correct positioning, assembly, and constriction of the FtsZ ring (Z-ring). Z-ring constriction control remains poorly understood and (to some extent) controversial, probably due to the fact that this phenomenon is transient and controlled by numerous factors. Here, we characterize ZapE, a novel ATPase found in Gram-negative bacteria, which is required for growth under conditions of low oxygen, while loss of zapE results in temperature-dependent elongation of cell shape. We found that ZapE is recruited to the Z-ring during late stages of the cell division process and correlates with constriction of the Z-ring. Overexpression or inactivation of zapE leads to elongation of Escherichia coli and affects the dynamics of the Z-ring during division. In vitro, ZapE destabilizes FtsZ polymers in an ATP-dependent manner. IMPORTANCE Bacterial cell division has mainly been characterized in vitro. In this report, we could identify ZapE as a novel cell division protein which is not essential in vitro but is required during an infectious process. The bacterial cell division process relies on the assembly, positioning, and constriction of FtsZ ring (the so-called Z-ring). Among nonessential cell division proteins recently identified, ZapE is the first in which detection at the Z-ring correlates with its constriction. We demonstrate that ZapE abundance has to be tightly regulated to allow cell division to occur; absence or overexpression of ZapE leads to bacterial filamentation. As zapE is not essential, we speculate that additional Z-ring destabilizing proteins transiently recruited during late cell division process might be identified in the future.